If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(4b + 4) + (33b + -5) = 0 Reorder the terms: -8(4 + 4b) + (33b + -5) = 0 (4 * -8 + 4b * -8) + (33b + -5) = 0 (-32 + -32b) + (33b + -5) = 0 Reorder the terms: -32 + -32b + (-5 + 33b) = 0 Remove parenthesis around (-5 + 33b) -32 + -32b + -5 + 33b = 0 Reorder the terms: -32 + -5 + -32b + 33b = 0 Combine like terms: -32 + -5 = -37 -37 + -32b + 33b = 0 Combine like terms: -32b + 33b = 1b -37 + 1b = 0 Solving -37 + 1b = 0 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '37' to each side of the equation. -37 + 37 + 1b = 0 + 37 Combine like terms: -37 + 37 = 0 0 + 1b = 0 + 37 1b = 0 + 37 Combine like terms: 0 + 37 = 37 1b = 37 Divide each side by '1'. b = 37 Simplifying b = 37
| 3(-6x-5y-7z-6)= | | 5.2q-4.5-4.6q=-0.4q-5.1 | | -89=-64 | | 6z-13=31 | | 6z-13=13 | | 1-(49/8) | | 1+(49/8) | | m-35=-41 | | (7/8)*7 | | (1/7)*7 | | 1/2(6x-4)=4-9 | | 4(7x+6y-6z)= | | (7x+7/8)(7x-1/7) | | 5(-12-32)/9= | | -9+3+2(a)=-2 | | -5x-7=-4x-8 | | 7x+5=-11x-13 | | 3x=6x-12 | | 8-4a=-8 | | -7x-5=-3x-13 | | -5x+5=3x-11 | | 12x+5=8x-7 | | x^5/8*x^3/8 | | 3a+4=7a-12 | | -12x+5=3x-10 | | -16=-2c | | -6=-2c | | 1/3-a=2 | | (2x-5)(x+5)=0 | | (2x+5)(x-5)=0 | | (2x+1)(x-25)=0 | | (6x+27)(9x+1)=0 |